Is the NFL's Pro Bowl broken? Considering the players' perspective - Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2021)
This paper examines the growing trend of NFL players to forego participation in the league's yearly All-Star Game, the Pro Bowl. Viewership of the Pro Bowl has been substantially lower than the average game day in recent years, causing controversial discussions about the viability of the game and its future. Since the major determinant of viewership demand is the participation of (superstar) players, this paper analyzes the individual athletes' economic incentives in the decision to participate. To this end, it models the athlete's decision as a rational evaluation of cost-benefit under incentives of monetary reward and punishment. It uses unbalanced panel data on Pro Bowl players from the Super Bowl era (1971-2019), alongside viewership data and official league data. It applies a range of econometric methods (Pearson-correlations, graphical examination) to evaluate hypotheses about the players' decision-making process. It concludes that the incentives to participate in the Pro Bowl for the majority of players, esp. viewership-driving superstar players are weak. The monetary incentives in their current form are not an efficient way of positively manipulating the percentage of superstars in the game. If the goal is higher demand from players, the incentive structure must be changed. Such changes are inter alia, that the positive reputational effects of a Pro Bowl title should be tied to participation, not selection. To increase the monetary incentive, the direct payouts should be adjusted for their relative loss compared to the general income level in the league.
Keywords: Z2; Z22; Z28; D8; 330; sports economics; pro bowl; national football league; league management